Deriving the dependence structure of portfolio credit derivatives using evolutionary algorithms - Svenja Hager; Rainer Schöbel (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2006)
Even if the correct modeling of default dependence is essential for the valuation of portfolio credit derivatives, for the pricing of synthetic CDOs a one-factor Gaussian copula model with constant and equalpairwise correlationsfor all assets in the reference portfolio has become the standard market model. If this model were a re?ection of market opinion, there wouldn't be the implied correlation smilethatis observedinthe market. Thepurposeof thispaperistoderive a correlation structure from observed CDO tranche spreads. The correlation structure is chosen such that all tranche spreads of the traded CDO can be reproduced. This implied correlation structure can then be used to price o?-market tranches with the same underlying as the traded CDO. Using this approach we can significantly reduce the risk to misprice o?-market derivatives. Due to the complexity of the optimization problem we apply Evolutionary Algorithms.
urn:nbn:de:bsz:21-opus-21859
Keywords: 330; Finanzderivat; Kreditsicherung; Wertpapieranalyse; Portfolio-Management; Evolutionärer Algorithmus; Theorie